The Black Atlantic : Modernity and Double-Consciousness - Gilroy, Paul (Verso, 1993)
To the forces of cultural nationalism hunkered down in their camps, this bold hook sounds a liberating call. There is, Paul Gilroy tells us, a culture that is not specifically African, American, Caribbean, or British, but all of these at once, a black Atlantic culture whose themes and techniques transcend ethnicity and nationality to produce something new and, until now, unremarked. Challenging the practices and assumptions of cultural studies, The Black Atlantic also complicates and enriches our understanding of modernism.
English
Keywords: Afrocentrism; Eurocentrism. Caribbean Studies. British Studies; HN50-995 Social history and conditions. Social problems. Social reform- By region or country